Weighted curvature-preserving PDE image filtering method. (September 2015) - Tian, Wei; Ma, Tinghuai; Zheng, Yuhui; Wang, Xin; Tian, Yuan; Al-Dhelaan, Abdullah; Al-Rodhaan, Mznah
Abstract The tensor-driven curvature-preserving partial differential equation is an outstanding anisotropic diffusion filtering model. To effectively preserve image edge well, a weighted curvature-preserving PDE based filtering method is proposed, which employ local image directional information to design weight coefficient for different vector fields. Experimental results indicate that new approach shows superior performance on preserving image edge and curvature geometric structure.